(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2003)
The analysis of the data of deposits exploration and exploitation of the marked industrial types allows to group and to define possible limits of various errors committed at realization of prospecting works - mistakes of analogy, technical and errors connected to wrong treatment of a deposits geological structure. The questions of reduction of the typical mistakes committed at exploration of non-ferrous metals deposits are consecrated.